Ocean acidification weakens the immune response of blood clam through hampering the NF-kappa β and toll-like receptor pathways. (July 2016) - Liu, Saixi; Shi, Wei; Guo, Cheng; Zhao, Xinguo; Han, Yu; Peng, Chao; Chai, Xueliang; Liu, Guangxu
Abstract: The impact of p CO2 driven ocean acidification on marine bivalve immunity remains poorly understood. To date, this impact has only been investigated in a few bivalve species and the underlying molecular mechanism remains unknown. In the present study, the effects of the realistic future ocean p CO2 levels (pH at 8.1, 7.8, and 7.4) on the total number of haemocyte cells (THC), phagocytosis status, blood cell types composition, and expression levels of twelve genes from the NF-kappa β signaling and toll-like receptor pathways of a typical bottom burrowing bivalve, blood clam ( Tegillarca granosa ), were investigated. The results obtained showed that while both THC number and phagocytosis frequency were significantly reduced, the percentage of red and basophil granulocytes were significantly decreased and increased, respectively, upon exposure to elevated p CO2 . In addition, exposure to p CO2 acidified seawater generally led to a significant down-regulation in the inducer and key response genes of NF-kappa β signaling and toll-like receptor pathways. The results of the present study revealed that ocean acidification may hamper immune responses of the bivalve T. granosa which subsequently render individuals more susceptible to pathogens attacks such as those from virus and bacteria. Graphical abstract: Highlights: OA leads to a reduction in total number of haemocyte cells and phagocytosis. Exposure to p CO2 acidified seawater alters blood cell type composition. OA generally down-regulates key genes of NF-kappa β signaling pathway. Exposure to p CO2 acidified seawater hampers toll-like receptor pathways. Ocean acidification weakens immune responses of blood clam.